2019
DOI: 10.3390/ma12030504
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Silk Fibroin for Biomedical Applications

Abstract: Three-dimensional (3D) printing is regarded as a critical technological-evolution in material engineering, especially for customized biomedicine. However, a big challenge that hinders the 3D printing technique applied in biomedical field is applicable bioink. Silk fibroin (SF) is used as a biomaterial for decades due to its remarkable high machinability and good biocompatibility and biodegradability, which provides a possible alternate of bioink for 3D printing. In this review, we summarize the requirements, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 118 publications
0
68
0
Order By: Relevance
“…Substrate stiffness has been known to alter the dynamics of cardiomyocytes 15,29b. Previous studies have shown that substrates encapsulating cardiomyocytes when mimicking the elasticity and strength of the developing myocardial environment were able to encourage actin‐myosin cytoskeleton development and 1 Hz beating in encapsulated cardiomyocytes .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Substrate stiffness has been known to alter the dynamics of cardiomyocytes 15,29b. Previous studies have shown that substrates encapsulating cardiomyocytes when mimicking the elasticity and strength of the developing myocardial environment were able to encourage actin‐myosin cytoskeleton development and 1 Hz beating in encapsulated cardiomyocytes .…”
Section: Resultsmentioning
confidence: 99%
“…Amongst the naturally available biomaterials, silk fibroin (SF), merits its application in tissue engineering due to its several desirable qualities. SF is a mechanically robust, exceptionally resilient, biodegradable material and manifests minimal immunogenic response in comparison to synthetic polymers . Therefore, SF protein has become a popular choice as a biomaterial ink for printing several tissues such as cartilage, bone and skin 15,18a,19.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the complexity of 3D-printing procedures, currently only simple structures can be printed. However, as printing techniques advance steadily, the construction of complex and multifunctional structures will be possible in the near future (32).…”
Section: Discussionmentioning
confidence: 99%